Факторы развития мировой морской торговли энергоресурсами - Гуцу, Г.И. (Економічні інновації, 2009)
Розглядаються фактори, що впливають на обсяги світової торгівлі нафтою, нафтопродуктами та скрапленим газом. Розглянуто прогнози які було розроблено у 2007-2008 роках щодо обсягів споживання, видобутку й морських перевезень та перспективи їх реалізації після відновлення світової економіки. Article presents the factors, which influence on the volumes of the world trading in crude oil, petroleum products and condensed gas. Presents prognoses, which were forecasted in 2007-2008 years in relation to the volumes of consumption, recovery and marine transportations and prospect of their realization after rehabilitation of a world economy.